The implementation of primary school science flipped classroom in Sabah: A case study - Mohd. Fadzly Wasriep (2022)
The flipped classroom is one of the approaches used in 21st-century teaching practices. Contrary to primary education, various literature on the flipped classroom approach was studied in the secondary and tertiary education levels. The study's literature comprised the sociocultural theory, constructivist theory of learning, zone of proximal development (ZPD), scaffolding in learning and models, and past studies on the flipped classroom. Based on the literature, some problems such as lack of science learning time in the classroom, lack of active learning, and lack of ICT use in learning can be mitigated by implementing a flipped classroom. Since the literature on primary school flipped classroom is limited, findings are needed. Thus, continuing the contribution to the body of knowledge, this research aims to explore the main themes in conducting a flipped-classroom approach in the context of primary school science. From the selection of teachers and learners, interviews, classroom observations, and document reviews were analysed systematically. Four schools were involved in this study. There were four teachers and twenty learners who have experience with flipped learning and agreed to be the informants. This study used within-case data analysis to analyse the four cases one by one, followed by crosscase data analysis to compare and contrast the four cases' findings. The findings reveal six themes in primary science flipped classroom implementations: pre-class session, in-class session, post-class session, affordance and assistance, barriers and mitigation plan. There are various aspects taken into consideration from the teacher and learners to implementing the flipped classroom. The teachers realised that although flipped classrooms helped them conduct the lesson in many ways, they need to resolve barriers. Indeed, the flipped classroom has promoted science learning through active learning activities in the classroom. At the same time, ICT is supplementary rather than compulsory. These findings provided a foundation for preliminary direction in implementing the primary school science flipped classroom and other researchers to do further study.